2019
DOI: 10.1016/j.abb.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SIRT1 by microRNA-9, the key point in process of LPS-induced severe inflammation

Abstract: Severe inflammation may lead to multiple organs dysfunction syndrome, which has a high mortality. MicroRNA is found participated in this process. In this study we developed a lipopolysaccharide-induced inflammation cell model on macrophages and a lipopolysaccharide-induced inflammation mouse model. It was found that during inflammation, microRNA-9 was increased, accompanied with the up-regulation of pro-inflammatory cytokines and anti-inflammatory cytokines. Down-regulation of microRNA-9 inhibited the up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…miR-9 has been previously shown to specifically target Sirt1 in macrophages, preventing Sirt1 from S1. 31, 107585, May 5, 2020 11 Article ll OPEN ACCESS deacetylating and inhibiting NF-kB, possibly leading to a feedforward loop, increasing miR-9 expression (Cao et al, 2018). Other studies have linked miR-9 with regulation of the chromatin landscape in neural progenitors through its action on Rest, and its corepressor Rcor1, which were also regulated by miR-9 in DCs (Packer et al, 2008;Delaloy et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-9 has been previously shown to specifically target Sirt1 in macrophages, preventing Sirt1 from S1. 31, 107585, May 5, 2020 11 Article ll OPEN ACCESS deacetylating and inhibiting NF-kB, possibly leading to a feedforward loop, increasing miR-9 expression (Cao et al, 2018). Other studies have linked miR-9 with regulation of the chromatin landscape in neural progenitors through its action on Rest, and its corepressor Rcor1, which were also regulated by miR-9 in DCs (Packer et al, 2008;Delaloy et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-9 is dynamic and has been observed to be upregulated in human monocytes and neutrophils when stimulated with LPS (Bazzoni et al, 2009;Lu et al, 2019;Thulin et al, 2013). In macrophages, inhibition of miR-9 leads to a reduction of organ damage in a model of severe LPS-induced inflammation (Cao et al, 2018). Specifically in DCs, microRNA profiling of activated human DCs revealed that miR-9 is upregulated upon LPS stimulation (Stumpfova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that SIRT1 to be a target of miR-9 (Bu et al, 2017;Cao et al, 2018;D'Adamo et al, 2017). To confirm that miR-9 could target SIRT1 in mouse-derived RAW 264.7 macrophages, we used TargetScan browser to predict the binding site of SIRT1 and miR-9.…”
Section: Overexpression Of Sirt1 Reversed Mcpip1 Knockdown-mediated Inflammatory Response and Nf-κb P65 Acetylation Changementioning
confidence: 99%
“…Together, these results demonstrated that miR-9 was negatively regulated by MCPIP1 and overexpression of miR-9 reversed MCPIP1-mediated inflammatory response. It was reported that SIRT1 to be a target of miR-9 (Bu et al, 2017;Cao et al, 2018;D'Adamo et al, 2017). To confirm that miR-9 could target SIRT1 in mouse-derived RAW 264.7 macrophages, we used TargetScan browser to predict the binding site of SIRT1 and miR-9.…”
Section: Mcpip1-mediated Nf-κb P65 Nuclear Translocation Through Regu...mentioning
confidence: 99%
“… 8 MiR-9 increased LPS-induced inflammatory response of macrophages by targeting silent information regulator 1 (SIRT1). 9 Moreover, a number of miRNAs regulate elements of the TLR-signalling cascade or target cytokines directly. MiR-146b directly targets IL-1 receptor-associated kinase 1 (IRAK1) and TNF receptor-associated factor 6 (TRAF6), key adaptor proteins of the TLR4/NF-κB signalling cascade, resulting in inhibition of NF-κB activation and inflammatory cytokine production.…”
Section: Introductionmentioning
confidence: 99%